IMPLEMENTATION OF STANDARD OPRATING PROCEDURES MAKE UP ROOM AT THE ROYAL ASNOF HOTEL PEKANBARU - Septia Ronald Riawansyah; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Hospitality is a commercial business that provides accommodation facilities such as lodging and food and beverage service facilities. Hospitality industry is a commercial industry that operates in the field of services that is very influential on the development of tourism in Indonesia. Hotel include business presses on sales of service. One of the activities undertaken by the company to achieve sales goals is to implement good and efficient service customer. without this kind of service efforts to increase sales volume is very difficult because of the many and tight competition that accurs today. this study aim to implementtation of standard oprating procedures make up room at the Royal Asnof Hotel Pekanbaru. This research uses qualitative description merthod to examine the problem in the lift by guest complain about to implementtation of standard oprating procedures make up room at the Royal Asnof Hotel Pekanbaru. while the data collection techniques in this study used interview, observation and documentation. The results of this study that form the implementation standard oprating procedure make up room Hotel Royal Asnof Pekanbaru its good enough but in roomboy there are still those who haven’t implementation it according to standart oprasional procedure make up room because the working equipment is not good enough to support the work of roomboy. Keywords: standart oprasional procedure make up room, roomboy, hotel